The effects of two different swimming training periodization on physiological parameters at various exercise intensities - Clemente-Suarez, V. J.; Dalamitros, A.; Ribeiro, J.; Sousa, A.; Fernandes, R. J.; Vilas-Boas, J. P. (European Journal of Sport Science, 2017)
This study analysed the effects of two different periodization strategies on physiological parameters at various exercise intensities in competitive swimmers. Seventeen athletes of both sexes were divided to two groups, the traditional periodization (TPG, n = 7) and the reverse periodization group (RPG, n = 10). Each group followed a 10-week training period based on the two different periodization strategies. Before and after training, swimming velocity (SV), energy expenditure (EE), energy cost (EC) and percentage of aerobic (%Aer) and anaerobic (%An) energy contribution to the swimming intensities corresponding to the aerobic threshold (AerT), the anaerobic threshold (AnT) and the velocity at maximal oxygen uptake (vVO2max) were measured. Both groups increased the %An at the AerT and AnT intensity (P = .05). In contrast, at the AnT intensity, EE and EC were only increased in TPG. Complementary, %Aer, %An, EE and EC at vVO2max did not alter in both groups (P > .05); no changes were observed in SV in TPG and RPG at all three intensities. These results indicate that both periodization schemes confer almost analogous adaptations in specific physiological parameters in competitive swimmers. However, given the large difference in the total training volume between the two groups, it is suggested that the implementation of the reverse periodization model is an effective and time-efficient strategy to improve performance mainly for swimming events where the AnT is an important performance indicator.